PENGGALANGAN DANA WAKAF TUNAI MELALUI CROWDFUNDING DI PT. AMMANA FINTEK SYARI`AH INDONESIA - Muhammad Alwi Sihab Bashari (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2021)
or case study which in this study looks for facts about raising cash waqf funds through crowdfunding and looking for factual information which in this study looks at the social phenomenon of raising cash waqf funds through crowdfunding in PT Amanah Fintek. The type of data used in empirical research comes from primary and secondary data, primary data is data that is directly obtained from informants through interviews, observations and documentation, while secondary data is used as supporting data, to check the validity of research data using triangulation. The cash waqf fundraising system offered by PT Ammana Fintek is a waqf fundraising by using an application that can make it easier for wakifs to do waqf besides that with a small nominal, the wakif can already do waqf so that it can attract people to do waqf, the method used by PT Ammana This fintech is a direct fundraising method in which PT Ammana Fintek uses techniques or methods that involve the participation of the waqif directly by using an application where the interaction process and the accommodation power of the waqif response can be carried out immediately (directly) if the waqif has desire to make a donation after getting a promotion from the institution's fundraiser.